2016
DOI: 10.1038/srep20069
|View full text |Cite|
|
Sign up to set email alerts
|

Group A Streptococcus exploits human plasminogen for bacterial translocation across epithelial barrier via tricellular tight junctions

Abstract: Group A Streptococcus (GAS) is a human-specific pathogen responsible for local suppurative and life-threatening invasive systemic diseases. Interaction of GAS with human plasminogen (PLG) is a salient characteristic for promoting their systemic dissemination. In the present study, a serotype M28 strain was found predominantly localized in tricellular tight junctions of epithelial cells cultured in the presence of PLG. Several lines of evidence indicated that interaction of PLG with tricellulin, a major compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 48 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…E-cadherin promoted the cell-to-cell adhesion and integrity of the epithelial barrier, and, accordingly, GAS translocation across epithelial monolayers was suppressed by the knockout of slo or nga. Sumitomo et al have reported that streptolysin S and a cysteine protease contribute to bacterial translocation by perhaps directly destabilizing intercellular junction proteins such as E-cadherin [39,42,44]. Our data suggest that invading GAS may support the translocation of extracellular GAS and may facilitate invasion into deeper tissues.…”
Section: Discussionmentioning
confidence: 54%
“…E-cadherin promoted the cell-to-cell adhesion and integrity of the epithelial barrier, and, accordingly, GAS translocation across epithelial monolayers was suppressed by the knockout of slo or nga. Sumitomo et al have reported that streptolysin S and a cysteine protease contribute to bacterial translocation by perhaps directly destabilizing intercellular junction proteins such as E-cadherin [39,42,44]. Our data suggest that invading GAS may support the translocation of extracellular GAS and may facilitate invasion into deeper tissues.…”
Section: Discussionmentioning
confidence: 54%
“…GAS infection studies in animals have provided strong evidence that GAS has the ability to manipulate the host fibrinolytic system at many levels [88,89]. On one hand, hijacking the host Plg/Plm on the bacterial surface has provided an energy-efficient strategy to break down the fibrin network during dissemination [55,57,90], and this is achieved with the aid of PAM. Using GAS strains which express both SK2b and PAM genes, it was shown that inactivation of either genes significantly reduces virulence [59].…”
Section: Resultsmentioning
confidence: 99%
“…Association and dissociation reactions of GP96 to pneumococcal Ali proteins were analyzed using a BIAcore optical biosensor (BIAcore X-100 system, GE Healthcare Life Sciences), as previously described 48 . Briefly, recombinant GP96 (20 g ml -1 in 10 mM sodium acetate, pH 4) was covalently immobilized on a CM5 sensor chip using an Amine coupling kit (GE Healthcare immobilized bacterial surface proteins for 90 minutes at 37ÂșC.…”
Section: Surface Plasmon Resonance Analysismentioning
confidence: 99%